Physical-hydraulic soil attributes in an integrated production system with different “paricá” forest component arrangements - Magalhães, Wellington de Azambuja; Freddi, Onã da Silva; Lange, Anderson; Wruck, Flávio Jesus; Silva, Wininton Mendes; Soares, Matheus Bortolanza (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to compare the structural quality and water retention curve of a Haplustox under single, double, and triple “paricá” (Ochroma pyramidale) lines in an integrated production system at 50 months of implantation. Soil was collected from five sampling points considering the distances from the tree lines. Undisturbed samples were collected from the 0.00–0.10 and 0.10–0.20-m layers in order to assess porosity, density, soil penetration resistance, soil water retention curve, and the “S” index. The forest arrangement based on three paricá lines promoted better soil physical conditions than the system using single lines. The main changes were recorded in the 0.10–0.20-m layer, with increased microporosity and decreased cryptoporosity and resistance to penetration. The arrangements using single and double paricá lines result in higher volume of available water and greater soil compaction.